Bread waste to lactic acid: Applicability of simultaneous saccharification and solid state fermentation. (March 2021) - Sadaf, Ayesha; Kumar, Sumit; Nain, Lata; Khare, Sunil Kumar
Abstract: On a global scale, food waste generation has set an alarming signal demanding its proper management and utilization. The present study investigates different types of bakery wastes used as a source of the high amount of reducing sugars for lactic acid production. As a result, bread waste (BW) containing 598 mg, reducing sugars/g waste was used for lactic acid production from several lactic acid bacteria (LAB). Out of these, SKL-9 ( Lactobacillus paracasei ), SKL-11 ( Lactobacillus paracasei ), and SKL-21 ( Lactobacillus paracasei ) were found to produce 53 mg/g BW (26.4 g/L), 56 mg/g BW (28 g/L), and 54 mg/g BW (27 g/L) of lactic acid, respectively under simultaneous saccharification and fermentation conditions. The selected strains were further tested for simultaneous saccharification and solid state fermentation (SSF) under semi-sterile conditions yielding 212, 223, and 250 mg/g BW of lactic acid by SKL-9, SKL-11, and SKL-21, respectively. Furthermore, the lactic acid produced was purified by employing the phase partitioning method giving a high recovery of 85%. Thus, the current approach is promising for the valorization of bakery waste into value-added lactic acid in an inexpensive one-pot process. Highlights: Bakery waste valorization for production of 250 mg/g of lactic acid. Simultaneous saccharification and solid-state fermentation was performed. The process was completed under semi-sterile conditions. Downstream processing of lactic acid by phase partitioning led to 85% recovery. Purified lactic acid was of L-form as confirmed by spectroscopy.